The Analysis of Recovery Implementation for Domestic Violence Victims - Suchmasasi, Yudha; Sutiyoso, Bambang Utoyo; Puspawati, Ani Agus (Journal of Research in Social Science and Humanities, 2021)
In Indonesia, the most common forms of domestic violence experienced are physical, sexual, psychological and economic neglect. As a result, it can cause physical and psychological injuries. Therefore, it is important to pay attention to the victim's recovery in order to strengthen the victim to be more empowered, both physically and psychologically. This article aims to describe and analyze the recovery implementation for domestic violence victims in Indonesia using the literature review method. The recovery implementation of domestic violence victims is carried out by building communication between relevant stakeholders so that cooperation is established in providing services to victims of domestic violence in accordance with their respective duties and responsibilities. The participation of external parties such as NGOs or women's organizations can assist in providing protection and assistance so that victims can still benefit from the policy even though there are still limitations from the government. The benefits of counseling services can help victims to grow confidence in living life. Empowerment through training can provide provisions for a more independent life. Obstacles faced by the government include: limited budget for handling cases of violence, especially violence against women; the number of assistants and counselors in some areas is still lacking; many room of special service facilities are inadequate and the distribution of safe houses is not evenly distributed in each area.